Applicability of UNCLOS for Landlocked states: The case of Chabahar port and Afghanistan. (2nd January 2021) - Kumar S, Sundeep
ABSTRACT: As a landlocked country, Afghanistan has been given special privileges by the United Nations Convention on the Law of the Sea (UNCLOS) to access seaports through transit states. Pakistan, as a transit state to Afghanistan, has violated such provisions of international treaties on many counts by blocking transit routes for trade with India and by denying access to its Karachi Port. India's Chabahar Port project in Iran acts as an alternative for Afghanistan to trade and aims to reduce its vulnerability of being dependent on Pakistan. This article attempts to highlight the India–Iran–Afghanistan trilateral understanding in Chabahar as an example of multilateral cooperation in fulfilling commitments made to international regimes, such as the UNCLOS, while bringing out the geopolitical challenges that India faces to complete the Chabahar project. In this context, the aim is to study the applicability of UNCLOS for rights of landlocked states and the importance of the Chabahar Port in protecting Afghanistan's commercial freedom. The article also highlights India's role in the region as it is responsible for implementing the Chabahar Port project.